Margins of International Banking: Is There a Productivity Pecking Order in Banking, Too? - Claudia M. Buch; Catherine Koch; Michael Koetter (Verein für Socialpolitik, 2010)
Modern trade theory emphasizes firm-level productivity differentials to explain the cross-border activities of non-financial firms. This paper tests whether a productivity pecking order also determines international banking activities. We use a novel dataset of all German banks' international activities to estimate the ordered probability of being present abroad (extensive margin) and the volume of international assets (intensive margin). Methodologically, we enrich the conventional Heckman selection-model to account for the self-selection of banks into different modes of foreign activities based on an ordered probit. Our paper has four main findings. First, as for non-financial firms, we find a productivity pattern order driving bank internationalization. Second, while only a few non- financial firms engage in international trade, many banks hold international assets. Only a few large banks engage in FDI. Third, apart from productivity, risk factors matter for international banking. Fourth, gravity-type variables have an important impact on international banking activities.
Keywords: F34; G21; F12; 330